Penerapan BIM dalam Simulasi Evakuasi pada Desain Tangga Evakuasi Gedung Baru PMI Jakarta - Ramadhan, Fadhlan Ihsan; Purnomo, Adhi; Khanza, Mirara (Jurnal Talenta Sipil, 2025)
The new PMI Jakarta building is a healthcare facility and staff office of PMI, established by the Jakarta Provincial Government. This new 10-story building has a total area of 12,554 square meters and is designed to accommodate 28 people per square meter. Due to its function, the building will be used with a high occupancy density. This density is related to evacuation time in case of emergencies such as earthquakes or fires. With the advancement of Building Information Modeling (BIM) technology, emergency evacuation within the building can be simulated using crowd simulation. This article aims to provide information on how BIM is applied to simulate emergency evacuation on the evacuation stairs designed for the new PMI Jakarta building. The results obtained show that the time required to evacuate all building occupants using the available evacuation stairs is 214.3 seconds or 3 minutes and 57 seconds. With BIM technology, evacuation simulation can be implemented in the planning stage of a building. This technology helps determine the outcome of a design when various evacuation scenarios are applied, such as estimating the time required to evacuate all occupants and identifying the fastest and safest evacuation routes.